Characterization of the mgl operon of Escherichia coli by transposon mutagenesis and molecular cloning. - Harayama, S (1983)
We used transposon insertion mutagenesis, molecular cloning, and a novel procedure for in vitro construction of polar and nonpolar insertion mutations to characterize the genetic organization and gene products of the beta-methylgalactoside (Mgl) transport system, which utilizes the galactose-binding protein. The data indicate that the mgl operon contained three genes, which were transcribed in the order mglB, mglA, and mglC. The first gene coded for the 31,000 Mr galactose-binding protein, which was synthesized as a 3,000-dalton-larger precursor form. The mglA product was a 50,000 Mr protein which was tightly associated with the membrane, and the mglC product was a 38,000 Mr protein which was apparently loosely associated with the membrane and was probably located on the internal face of the cytoplasmic membrane. Identification of gene products was facilitated by in vitro insertion of a fragment of Tn5 containing the gene conferring kanamycin resistance into a restriction site in the operon. The fragment proved to have a polar effect on the expression of promoter-distal genes only when inserted in one of the two possible orientations. The three identified gene products were necessary and apparently sufficient for transport activity, but only the binding protein was required for chemotaxis towards galactose. The transport system appeared to contain the minimum number of components for a binding protein-related system: a periplasmic recognition component, a transmembrane protein, and a peripheral membrane protein that may be involved in energy linkage.